2012
DOI: 10.1590/s1807-55092012000100012
|View full text |Cite
|
Sign up to set email alerts
|

Aprendizagem de uma habilidade motora seriada em diferentes estágios de desenvolvimento

Abstract: Este estudo investigou a aprendizagem de uma tarefa motora seriada em diferentes estágios de desenvolvimento. Quinze crianças, 14 adultos e 13 idosos praticaram a tarefa de rastrear uma sequência de seis estímulos luminosos durante 10 blocos de tentativas ou até descobrir a sequência, constituindo a fase de estabilização e mais dois blocos de tentativas, referentes as fases de adaptação I e II. O desempenho foi mensurado por meio das respostas funcionais e não-funcionais e das sequências funcionais. Os resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Diniz et al 34 studied children, adults and elderly individuals during the learning of a serial task, which consisted of touching sensors with the index finger of the dominant hand, six times in response to light stimuli. The authors observed that adults had better responses than children and elderly, and only adults were able to learn the full sequence of the serial pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Diniz et al 34 studied children, adults and elderly individuals during the learning of a serial task, which consisted of touching sensors with the index finger of the dominant hand, six times in response to light stimuli. The authors observed that adults had better responses than children and elderly, and only adults were able to learn the full sequence of the serial pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The maze test has already been used to assess people with typical development (22), deficiency (15), and syndromes (23), as well as older adults (24).…”
Section: Introductionmentioning
confidence: 99%